Quality by Design Approach for Development and Optimization of Rifampicin Loaded Bovine Serum Albumin Nanoparticles and Characterization - Joshi, Monica; Yadav, Khushwant S.; Prabhakar, Bala (Current Drug Delivery, 2021)
Background: Rifampicin is one of the first-line drugs used for tuberculosis therapy. The therapy lasts for a long time. Thus, there is a need to develop a sustained release formulation of rifampicin for intravenous application. Aim: This study is focused on preparing rifampicin-loaded bovine serum albumin nanoparticles (RIF BSA NPs) suitable for intravenous application using systematic quality by design (QbD) approach. Objectives: The main objective of this study is optimizing particle size and entrapment efficiency of rifampicin-loaded bovine serum albumin nanoparticles (RIF BSA NPs) and making them suitable for intravenous application using QbD approach. Methods: Quality target product profile was defined along with critical quality attributes (CQAs) for the formulation. 32 factorial design was used for achieving the predetermined values of CQAs, i.e., mean particle size <200 nm and percent entrapment efficiency>50%. Incubation time of drug with colloidal albumin solution and ratio of rifampicin to albumin, were selected as independent variables. Checkpoint analysis was performed to confirm the suitability of the regression model for optimization. Results: The optimized RIF BSA NPs were characterized by FTIR, DSC, 1H NMR techniques. The NPs observed by transmission electron microscopy were spherical in shape. The rifampicin release could be sustained for 72 hours from BSA NPs matrix. RIF BSA NPs dispersion was stable at 5 ± 3°C for 72 hours. Non-toxicity of nanoparticles to RAW 264.7 cell line was proved by MTT assay. Conclusion: Development of RIF BSA NPs with desired quality attributes was possible by implementing the QbD approach. The optimized formulation suitable for intravenous application can potentially improve the therapeutic benefits of rifampicin.
Keywords: QbD